Awareness About Diabetes And Its Complications Among Patients With Diabetes Mellitus - Batool, Faiza; Malik, Kausar; Meraj, Lubna; Siddiq, Shazia; Majeed, Abbas; Khan, Sadia (Journal of Rawalpindi Medical College, 2023)
Objective: Awareness of diabetes and its potential complications is crucial for effective management and prevention of long-term health risks. This study aimed to assess the level of awareness and understanding of diabetes and its complications among patients diagnosed with type 2 diabetes mellitus. Methods: A cross-sectional study included 200 patients with type 2 diabetes mellitus as per the American Diabetes Association (ADA) criteria. Type 1 diabetes and gestational diabetes patients were excluded from the study. The duration of the study was 8 months. The patient’s awareness regarding diabetes and its complications was assessed as per the prefixed questionnaire. Analysis of the data was carried out with SPSS version 28. The Chi-square test was used to investigate the association of awareness of diabetes mellitus with various independent variables variable as age and duration of diabetes. The level of statistical significance was p <0.05. Results: Among the participants, 80 (40%) were male and 120 (60%) were female. A significant portion of patients 73 (36.5%) were never informed about diabetes or its complications. 69 (34%) of patients were never educated about the symptoms of hypoglycemia. 142 (71%) of the patients had a glucometer and 88 (44%) participants had poor follow-up and never checked HbA1C. Moreover, Patients with longer diabetes duration were more likely to visit ophthalmologists at regular intervals (P value 0.023). 111 (56%) never checked their urine for proteinuria and 172 (86%) were aware that diabetes can affect their kidneys. Foot care and awareness of diabetic foot complications were lacking among patients. 48 (24%) examined their feet daily, 66 (33%) never examined their feet, and 73 (36%) were never told about foot care by their doctors. The statistically significant impact of age on patients' knowledge regarding blood sugar levels (P=0.009) and foot care (P=0.013) Conclusion: There is a significant lack of awareness among individuals with diabetes, highlighting the urgent need for educational initiatives. Both the public and private healthcare sectors should take the responsibility of providing awareness programs. Keywords: Type 2 diabetes mellitus, awareness, complications.